It cannot be factored because the discriminant is less than zero.
Do you mean x2+11x-60 then if so it is (x-4)(x+15)
Chat with our AI personalities
6x2 + 11x - 10 = (6x2 + 15x) - (4x + 10) = 3x(2x + 5) - 2(2x + 5) = (3x - 2)(2x + 5). Note, first, that the three co-efficients of the original quadratic expression are 6, 11, and -10. We need two numbers whose sum is 11 and whose product is (6)(-10) = -60. These two numbers turn out to be 15 and -4. Thus, we replace the middle term, 11x with 15x - 4x and proceed with the factorisation in the usual way.
4507 5267 - 500 - 200 - 60 = 4507
Thirty plus thiry
x = 10
60 - 20 = 20 + 20=============